2006
DOI: 10.1295/polymj.pj2006042
|View full text |Cite
|
Sign up to set email alerts
|

π-Electronic Soft Materials Based on Graphitic Nanostructures

Abstract: ABSTRACT:This review focuses on our recent studies on the development of soft materials consisting of graphitic nanostructures. We found that single-walled carbon nanotubes, when suspended in imidazolium ion-based ionic liquids and ground in an agate mortar, form physical gels (bucky gels), where entangled nanotube bundles are exfoliated to give highly dispersed, much finer bundles. The use of polymerizable ionic liquids as the gelling media leads to the formation of highly electroconductive polymer/nanotube c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Recently, we reported self-assembled nanotubular objects of hexabenzocoronene (HBC) amphiphiles (e.g., 3 ) (Figure ), which consist of helically rolled bilayer tapes composed of bilaterally coupled columns of π-stacked HBC units . In the course of this study we noticed that under certain conditions coiled assemblies occasionally result together with the nanotubes.…”
Section: Introductionmentioning
confidence: 77%
“…Recently, we reported self-assembled nanotubular objects of hexabenzocoronene (HBC) amphiphiles (e.g., 3 ) (Figure ), which consist of helically rolled bilayer tapes composed of bilaterally coupled columns of π-stacked HBC units . In the course of this study we noticed that under certain conditions coiled assemblies occasionally result together with the nanotubes.…”
Section: Introductionmentioning
confidence: 77%
“…Additionally, there has now been interest in graphites or even graphene molecular sheets as fillers that combine high performance with moderate prices (10). Therefore, in addition to the already mentioned conductive fillers, expanded graphite (EG) was incorporated in nanocomposites as a representative of a platelet-like filler with a spectral dimension of d s ≈ 2.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Aida and co-workers [36][37][38][39][40][41] demonstrated the formation of one such HARNS by using an amphiphilic hexa-peri-hexabenzocoronene (hbc) that selfassembles in solvent to form a π-electronic, micrometre long, discrete nanotubular objects. The resulting tubes are characterized by an aspect ratio greater than 1000.…”
Section: Introductionmentioning
confidence: 99%